Blended learning approach in graduate studies: A bibliometric analysis from 1997-2021 - Omar, Rusdi; Kaliappen, Narentheren; Khamis, Kamarul Azman; Sulisworo, Dwi (CQUniversity, Australia / International Association of Computer Science and Information Technology, 2021)
Research on the blended learning approach in graduate studies has started since 1997. Thereafter, researchers in various subject areas have widely investigated the term blended learning. This paper thus seeks to analyze scientific literature, especially for graduate studies, published on the blended approach. All the literature published about blended approach in graduate studies was gathered using the Scopus database. The data was analyzed using Microsoft Excel. Standard bibliometric analysis was used to create the growth of publications and the citation analysis. A total of 801 documents were found based on the search results. Since 2004, the growth rate of literature on blended learning in graduate studies has accelerated radically. Journal articles and conference papers accounted for most of the publications, which were mostly written in English and Spanish. Most of the studies were conducted in the fields of social science and computer science. E-learning, online learning, collaborative learning and flipped classroom were among the most frequently used keywords. Most of the blended learning research in graduate studies was carried out in the United Kingdom, Australia, and the United States. This paper presents the literature's evolution in the blended learning approach in graduate studies and identifies current research interest and the potential future research direction.